The impact of structural and strategic competition on hospital quality - Christiane Wuckel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Many health care systems aim to enhance hospital quality by encouraging competition. However, evidence on the relationship between quality and competition is inconclusive. My contribution to this literature is two-fold. Analyzing the relationship between competition and quality for the German hospital market can give valuable insights about the nature of the relationship in a market with regulated prices that is characterized by a high number of hospitals and a diverse ownership structure. While most studies look at competition as market structure, I distinguish effects of market structure from effects of strategic behavior. I find evidence for a significant, non-linear relationship between market structure and care quality. Additionally, I find evidence for strategic behavior. – – Viele Gesundheitssysteme versuchen, die Qualität von Krankenhäusern Wettbewerbsanreize zu verbessern. Der Zusammenhang zwischen Qualität und Wettbewerb ist jedoch nicht eindeutig belegt und stark von der konkreten Ausgestaltung des jeweiligen Krankenhausmarktes abhängig. Die Analyse des Zusammenhangs zwischen Wettbewerb und Qualität für den deutschen Krankenhausmarkt kann wertvolle Erkenntnisse über die Art der Beziehung liefern in einem Markt mit regulierten Preisen, der durch eine hohe Anzahl von Krankenhäusern und einer vielfältigen Eigentümerstruktur gekennzeichnet ist. Während die meisten Studien den Wettbewerb als Marktstruktur betrachten, unterscheide ich Effekte der Marktstruktur von Effekten des strategischen Verhaltens. Ich finde Belege für eine signifikante, nicht-lineare Beziehung zwischen Marktstruktur und Versorgungsqualität. Außerdem finde ich Belege für strategisches Verhalten.
Keywords: C21; I11; L11; 330; Hospitals; quality; competition; spatial econometrics